HOW DO LEARNERS RESPOND TO CBL MATERIAL BASED ON MODALITY LEARNING STYLE? - Hassan, Razali; Hashim, Mohd Noor; Hj. Hussein, Atan (Journal of Technical Education and Training, 2010)
This is a report of case study exploring the reaction of learners to CBL material which has been purposely develop suited with learners based on VARK learning styles. It discusses the strengths and weaknesses of CBL and the concept of learning style. Courseware demonstrating the use of images and video clips within the presentation software PowerPoint was created with four different routes to appeal to learners with visual, aural, reading and kinaesthetic (VARK) preferences. This was trialled with 30 student teachers for whom the material was deemed appropriate in level and context. It was found that VARK preferences could not be reliably identified and that providing different routes only appeared to have a marginal impact on learners’ comfort with the material and no appreciable impact on measurable learning outcomes. Instead more traditional design concerns such as structure, navigation as well as clarity of sound and images appeared as more important to participants in the trials in a series of semi structured interviews. However, interest in VARK is valuable if it focuses the designer on using a mix of media in courseware and if it provokes discussion of the properties of different media.